Beauty unmasked the image and portrayal of Filipino women in selected beauty soap television advertisements from 1964-2013 - Santos, Alexandra Maria Francia P.; Santos, Josefina C.; University of the Philippines. College of Mass Communication (2014)
"The concept of beauty can be interpreted and defined in different ways depending on the individual's set of beliefs and/or philosophy. It is because of this subjectivity that the media, particularly thru advertising, is able to control, define and at times, even distort its meaning. The power of media, undoubtedly enables it to produce its own set of standards of beauty and consequently, impose them on its audience. This study addresses this very role of media and how its use defines the Filipino women, as seen and portrayed through the roles and images crafted in beauty soap television advertisements from 1964-2013. This study purposely makes use of the theories of Symbolic Interactionism, Saussure's Model of Signs and Postmodern Feminism in the reading and analysis of the said subject advertisements. Further, the use of Critical Discourse Analysis, helped reveal certain critical and problematic messages imbedded in the images and portrayals of women thru the years. It is likewise able to provide a more holistic view of women, given the social, political and economic context in which these advertisements were aired. This study shows that the advertisements, regardless of when they were made remained constant in the depiction of what a beautiful Filipino woman is or should be. The advertisements not only showed a homogenized image and portrayal of women of being young, carefree and beautiful, but also one who is subservient to the dictates of others. While there may be a noticeable shift in the depictions, i.e., from the passive voiceless woman to a more active and confident image of women, certain underlying ideologies run common in these commercials. The phrase "beauty lies in the eyes of the beholder" certainly rings true in the commercials reviewed, as they invariably defined beauty thru the eyes of others, particularly those of a man, a beauty stylist and by a celebrity. Unfortunately still, the advertisement zero-in on beauty that is not only skin deep but more alarmingly appears to be discriminatory as well. Thus, no matter how subtly, the message that comes across is for one to be beautiful, one has to be physically so, and in the land of brown-skinned people, be fairer than fair. Given the tremendous influence they have on society, media practitioners should find these insights useful, if only to come up and produce commercials that not only reshape the idea of beauty as to include inner beauty but one that is non-discriminatory and morally uplifting as well. Further, this study should help educate advertising audiences, especially women, so that they will be able to resist and thereafter challenge the messages that limit the formation of the Postmodern Feminist concept of a woman."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Women in advertising -- Philippines; Television commercials -- Philippines